Immunotherapies Targeting Tumor-Associated Macrophages (TAMs) in Cancer - Mei-Ye Li; Wei Ye; Ke-Wang Luo (MDPI AG, 2024)
Tumor-associated macrophages (TAMs) are one of the most plentiful immune compositions in the tumor microenvironment, which are further divided into anti-tumor M1 subtype and pro-tumor M2 subtype. Recent findings found that TAMs play a vital function in the regulation and progression of tumorigenesis. Moreover, TAMs promote tumor vascularization, and support the survival of tumor cells, causing an impact on tumor growth and patient prognosis. Numerous studies show that reducing the density of TAMs, or modulating the polarization of TAMs, can inhibit tumor growth, indicating that TAMs are a promising target for tumor immunotherapy. Recently, clinical trials have found that treatments targeting TAMs have achieved encouraging results, and the U.S. Food and Drug Administration has approved a number of drugs for use in cancer treatment. In this review, we summarize the origin, polarization, and function of TAMs, and emphasize the therapeutic strategies targeting TAMs in cancer treatment in clinical studies and scientific research, which demonstrate a broad prospect of TAMs-targeted therapies in tumor immunotherapy.